Extent of Ejection Fraction Improvement After Revascularization Associated with Outcomes Among Patients with Ischemic Left Ventricular Dysfunction - Wang S; Cheng S; Zhang Y; Lyu Y; Liu J (International Journal of General Medicine, 2022)
Shaoping Wang,1 Shujuan Cheng,1 Yuchao Zhang,1 Yi Lyu,2 Jinghua Liu1 1Department of Cardiology, Beijing Anzhen Hospital, Capital Medical University, Beijing Institute of Heart Lung and Blood Vessel Diseases, Beijing, People’s Republic of China; 2Department of Anesthesiology, Minhang Hospital, Fudan University, Shanghai, People’s Republic of ChinaCorrespondence: Jinghua Liu, Department of Cardiology, Beijing Anzhen Hospital, Capital Medical University, No. 2 Anzhen Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Tel +86 10 64456998, Fax +86 1064456998, Email liujinghua@vip.sina.com Yi Lyu, Department of Anesthesiology, Minhang Hospital, Fudan University, No. 180 Xinsong Road, Minhang District, Shanghai, 201199, People’s Republic of China, Email 19111360001@fudan.edu.cnPurpose: Ejection fraction (EF) has been reported to be a major predictor of improved survival in patients with heart failure. However, it is largely unknown whether the extent of improvement in EF affects the subsequent risk of mortality. This study sought to investigate change in EF after revascularization and the implication of these changes on clinical outcomes among patients with ischemic left ventricular dysfunction.Patients and Methods: We conducted a cohort study (No. ChiCTR2100044378) of patients with reduced EF (≤ 40%) who received revascularization and had EF reassessment by echocardiography 3 months after revascularization. Patients were categorized according to the absolute change in EF: 1) EF worsened group (absolute decrease in EF > 5%); 2) EF unchanged group (absolute change in EF − 5% to 5%); 3) EF improved group (absolute increase in EF > 5%).Results: Of 974 patients, 84 (8.6%) had EF worsened, 317 (32.5%) had EF unchanged and 573 (58.8%) had EF improved. The median follow-up time was 3.5 years, during which 143 patients died. For each 5-unit increments in EF, the risk of death decreased by 20% (hazard ratio, HR, per 5% increases, 0.80; 95% CI, 0.73– 0.86; P< 0.001). Compared with EF improvement group, patients with EF worsened (HR, 3.35; 95% CI, 2.07– 5.42; P< 0.001) and patients with EF unchanged (HR, 2.05; 95% CI, 1.40– 3.01; P< 0.001) had significantly higher risk of all-cause death.Conclusion: Changes in EF were inversely associated with the risk of mortality. The extent of EF improvement after revascularization might be a potential factor which defines clinical outcomes.Keywords: ejection fraction, left ventricular dysfunction, heart failure, revascularization